Favorable response of hepatocellular carcinoma with portal vein tumor thrombosis after radiotherapy combined with atezolizumab plus bevacizumab - Yong Tae Kim; Jina Kim; Jinsil Seong (Korean Liver Cancer Association, 2023)
Recently, the superiority of atezolizumab plus bevacizumab (AteBeva) over sorafenib was proven in the IMbrave150 trial, and AteBeva became the first-line systemic treatment for untreated, unresectable hepatocellular carcinoma (HCC). While the results are encouraging, more than half of patients with advanced HCC are still being treated in a palliative setting. Radiotherapy (RT) is known to induce immunogenic effects that may enhance the therapeutic efficacy of immune checkpoint inhibitors. Herein, we report the case of a patient with advanced HCC with massive portal vein tumor thrombosis treated with a combination of RT and AteBeva, who showed near complete response in tumor thrombosis and favorable response to HCC. Although this is a rare case, it shows the importance of reducing the tumor burden via RT to combination immunotherapy in patients with advanced HCC.